PELATIHAN PENGAJUAN JABATAN FUNGSIONAL MELALUI WEBSITE SIKOMING DI INSTITUT PENDIDIKAN NUSANTARA GLOBAL - Habibi, Ridwan; Muttaqin, Muh Zaini Hasanul; Rosyidi, Ahmad Zuhri (LPP ARROSYIDIN, 2023)
SIKOMING is the official website of LLDIKTI region VIII which is used for applications for functional lecturer positions in its work area. In its application, many problems arise, such as (a) lecturers do not understand Sikoming; (b) difficulty in filling out the form; (c) difficulty in producing documents as evidence. Of course, this is a concern so training needs to be held. In carrying out this community service, it is carried out through presentations, questions and answers, discussions and practice in filling out application forms via the SIKOMING website. The result of this training activity was that the participants successfully completed the functional position application form via the SIKOMING website. Apart from that, the participants also felt enthusiastic about taking part in the training.